Casebook of indigenous business practices in Africa. volume 2 : trade, production and financial services - Adeola, Ogechi (Bingley, U.K. : Emerald Publishing Limited, 2023)
Africa's unique and diverse culture, embedded in age-long business practices, presents an interesting proposition for advancing indigenous knowledge and building sustainable structures. Casebook of Indigenous Business Practices in Africa is a collection of case studies across Northern, Eastern, Central, Western and Southern parts of Africa. Indigenous enterprises contribute to the economic prosperity of Africa and are an essential part of the continent's business ecosystem. Contributing authors to this two-volume edited work explore the inherent potential of indigenous practices in bolstering business performance and stimulating social and economic development. The first volume focuses on Apprenticeship, Craft, and Healthcare, while this second volume considers Trade, Production and Financial Services, in featured African countries. Indigenous business practices hold great prospects for economic advancement in Africa, despite the dominance of Western business methods, which, although beneficial, are yet to drive the continent's developmental agenda. By identifying and exploring the unique features of these practices, multiple actors, including entrepreneurs, policymakers, students, educators, and practitioners, are provided with context-based information that can foster social and economic empowerment across the continent. The book extends the frontier of knowledge on the role of cultural orientation, values, and traditions in achieving a more prosperous Africa through the development of indigenous business knowledge.
Chapter 1. Introduction to casebook on indigenous business practices in Africa - volume ii trade, production, and financial services / Ogechi Adeola -- Part I. Indigenous trade practices and production -- Chapter 2. Challenges of indigenous black soap (Ọsẹ Dúdú) Entrepreneurs in Southwest Nigeria / Olayinka Akanle and Adedeji Adewusi -- Chapter 3. Preparation for business negotiation at the livestock auction market in tanzania: The case of maasai livestock traders / Felix Adamu Nandonde -- Chapter 4. Sustainability of indigenous butchery business in Ghana / Mohammed Majeed, Prince Gyimah, and Adiza Sadik -- Chapter 5. What is peculiar in the sustainability practices of indigenous female business owners in Uganda? / Patricia Isabirye -- Chapter 6. Informality, control/management practices and performance of small congolese enterprises: A focus on smes in the city of bukavu / Marcellin Chirimwami Luvuga, Deogratias Bugandwa Mungu Akonkwa, and Didier Van Caillie -- Part II. Indigenous financial practices -- Chapter 7. The ecosystem of indigenous savings and credit associations in sierra leone: Entrepreneurial success or nightmare? / Abdul Karim Kafoir and Emeka Raphael Agu -- Chapter 8. Structure of indigenous savings groups in nigeria: Cases and implications for business actors / Ogechi Adeola, Ifedapo Adeleye, Oserere Ibelegbu, Babalola Josiah Olajubu, and Isaiah Adisa -- Chapter 9. Exploring the financial literacy of a chama women's group in rural western Kenya / Lillian Zippora Omosa -- Chapter 10. Rotating stokvel model for entrepreneurial success in South Africa: Validation of constructs from a case study / Ishmael Obaeko Iwara and Ogechi Adeola -- Part III. Conclusions and recommendations -- Chapter 11. Internationalisation of indigenous agribusiness in Africa: The case of jr farms in rwanda and zambia / Belinda Nwosu and Edidiong Esara -- Chapter 12. Advancing Africa's indigenous business practices: Recommendations for educators and busine
Includes bibliographical references and index.
Print version record.
Keywords: Industrial management -- Africa -- Case studies; Corporate culture -- Africa -- Case studies; Business & Economics -- Management; Business studies: general